Comparación de dieta, propiedades salivales, hábitos de higiene oral y su asociación con caries dental en dos instituciones educativas de la comuna 8 Ibagué-Tolima - Candia Duran, Yessica Andrea; Carrillo Silvestre, Natalia Andrea; Páez Trujillos, Jessica Mayury (Universidad Antonio Nariño, 2021)
Introduction: diet, salivary properties and oral habits, the roles a fundamental role in the formation of dental caries, where children between the ages of 3 to 5 years are at high risk of developing early childhood caries. That's when assisted brushing, oral hygiene education that parents or guardians instill in children, an intake of healthy food according to age and the importance of making regular visits to the dentist are essential to prevent the appearance of caries. Objective: to compare diet, salivary properties, oral hygiene habits and its association with dental caries in two educational institutions of different levels (public and private) in community 8, Ibagué-Tolima. Methodology: In this study, the comparison of the previous variables related to the levels of glucose, cholesterol and triglycerides present in saliva was performed. The research was carried out at the Colegio Nuevo Liceo El Castillo (Private) and Hogar Infantil Arcoíris (Public) schools with a sample of 30 children who met the inclusion criteria for the study. A survey was carried out of the children and teachers in charge, anthropometric parameters were taken and a dental clinical examination was carried out using the index of decayed, extracted and filled teeth (CEO-d), and finally a salivary sample collection. Conclusion: that according to the results of this work, the children of the (public) institution have higher carbohydrate consumption, less help in assisted brushing, and the vast majority do not brush their teeth in the afternoon, and have higher carbohydrate consumption. , son with the highest caries index related to the children of the Private School.